1974
DOI: 10.1128/jb.120.2.934-944.1974
|View full text |Cite
|
Sign up to set email alerts
|

Co-Transduction of Plasmids Mediating Resistance to Tetracycline and Chloramphenicol in Staphylococcus aureus

Abstract: MATERIALS AND METHODS Bacterial strains and media. The source and properties of the staphylococci and their plasmids are listed in Table 1. We used the designations Cm, Tc, Sm, and Km for the phenotypes of resistance to chloramphenicol, tetracycline, streptomycin, and kanamycin. CY broth, 1%, a yeast extract-casein hydrolysate medium, was prepared according to Novick (24). Other media were commercial products. Plasmid elimination. For elimination of plasmids, two to three colonies of a culture grown on a brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
17
1

Year Published

1975
1975
1985
1985

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 30 publications
1
17
1
Order By: Relevance
“…1, the transduction frequency of pC194 by 411 was inversely proportional to the input MOI. At higher MOI (0.1 to 1 PFU/CFU), the transduction frequency was 10-7 to 10-6, which is in the expected range for transduction in Staphylococcus aureus (6,7,10,23,24,26). However, as the MOI decreased from 1 to 10-5 PFU per recipient, the transduction frequency increased dramatically to almost 10-2.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…1, the transduction frequency of pC194 by 411 was inversely proportional to the input MOI. At higher MOI (0.1 to 1 PFU/CFU), the transduction frequency was 10-7 to 10-6, which is in the expected range for transduction in Staphylococcus aureus (6,7,10,23,24,26). However, as the MOI decreased from 1 to 10-5 PFU per recipient, the transduction frequency increased dramatically to almost 10-2.…”
mentioning
confidence: 76%
“…This was first shown by Grubb et al (6,7), who demonstrated cotransduction of staphylococcal streptomycin resistance and tetracycline resistance plasmids. Later, Stiffler et al (26) and Iordanescu (10) extended this observation to include a variety of other small plasmids. These investigations highlight a dilemma that arises because cotransduction of plasmid DNA in Staphylococcus spp.…”
mentioning
confidence: 92%
“…Indeed, the use of the term "chromosome" with reference to S. aureus is quite properly qualified to refer to "the genophore(s) that corresponds to the chromosome in other bacteria" (9). As the sole means for direct genetic analysis in S. aureus until recently, generalized transduction has nonetheless been immensely useful for fine-structure genetic analysis (15) and for the genetic characterization of plasmids (8,24). Because of the limited size (8) and apparent homogeneity (14) of the transducing fragments, however, generalized transduction has been of limited value in studying the gross organization of the staphylococcal chromosome.…”
mentioning
confidence: 99%
“…The mechanism of the cotransduction of distinct plasmids is not yet clear. The plasmids found in cotransductants were reported to be independent and apparently identical with the original plasmids (5,15). Moreover, no co-integrate forms could be isolated from cells carrying cotransducible plasmids (14,15).…”
mentioning
confidence: 98%
“…The simultaneous transduction of several plasmid-borne markers represents an important argument for their presence on the same plasmid (1,13). The cotransduction of independent plasmids was, however, reported in several instances in Escherichia coli (2) as well as in Staphylococcus aureus (4,14,15). In S. aureus, only the plasmids belonging to the small-size class (12) carrying a single resistance marker seem to be implicated in cotransduction.…”
mentioning
confidence: 99%